2017
DOI: 10.3389/fimmu.2017.00815
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania infantum Parasites Subvert the Host Inflammatory Response through the Adenosine A2A Receptor to Promote the Establishment of Infection

Abstract: Adenosine is an endogenously released purine nucleoside that signals through four widely expressed G protein-coupled receptors: A1, A2A, A2B, and A3. Of these, A2AR is recognized as mediating major adenosine anti-inflammatory activity. During cutaneous leishmaniasis, adenosine induces immunosuppression, which promotes the establishment of infection. Herein, we demonstrated that A2AR signaling is exploited by Leishmania infantum parasites, the etiologic agent that causes Visceral Leishmaniasis, to successfully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…Inhibition of signal transduction via these receptors showed upregulation of proinflammatory cytokines and downregulation of anti-inflammatory cytokines, ultimately suppressing the intracellular persistence of Leishmania. Few studies have shown an individual contribution of adenosine receptors in infection (Figueiredo et al, 2017;Lima et al, 2017;Vijayamahantesh et al, 2016); however, the present study is perhaps the first to report the crucial role played by both A 2A R and A 2B R in the pathogenesis caused by L. donovani.…”
Section: Discussionmentioning
confidence: 48%
“…Inhibition of signal transduction via these receptors showed upregulation of proinflammatory cytokines and downregulation of anti-inflammatory cytokines, ultimately suppressing the intracellular persistence of Leishmania. Few studies have shown an individual contribution of adenosine receptors in infection (Figueiredo et al, 2017;Lima et al, 2017;Vijayamahantesh et al, 2016); however, the present study is perhaps the first to report the crucial role played by both A 2A R and A 2B R in the pathogenesis caused by L. donovani.…”
Section: Discussionmentioning
confidence: 48%
“…T. gondii infection dramatically increased A 3 AR mRNA and protein levels in a time-dependent manner but not those of A 1 R, A 2A AR, and A 2B AR. Lima et al previously reported that Leishmania infantum parasites subvert the host inflammatory response through adenosine A 2A receptor to promote the establishment of infection [ 20 ]. The greatest differences between these 2 studies are the infection source of different species.…”
Section: Discussionmentioning
confidence: 99%
“…For mice infected with Leishmania braziliensis , administration of adenosine increased lesion development and tissue parasitism [107], while blockage of P1-A2B receptors decreased lesion size and parasitic load [107]. In a murine model of Leishmania infantum infection, P1-A2A receptor signaling reduced activation and migration of neutrophils, allowing the establishment of infection [108].…”
Section: Purinergic Signalingmentioning
confidence: 99%